Immigrants Earning in Canada: Age at Immigration and Acculturation - Meng, YIng (Université d'Ottawa | University of Ottawa, 2014)
This paper uses 2006 Canadian census data to examine the effects of acculturation on the labour market performance of male immigrants in Canada (excluding Quebec). To achieve this, three variables that are supposed to affect the process of acculturation are incorporated in Mincer type earning regressions. These variables are age at immigration, country of birth and mother tongue. Results reveal that no matter where immigrants come from and whether or not they have English as their mother tongue, they do not have an earnings deficit if they arrive at a younger age. Younger immigrants acculturate more easily than older immigrants. Immigrants from the U.S., Europe and Oceania perform better in the labour market among all immigrants. Furthermore, the results that while not having English as mother tongue is a disadvantage to immigrants, it is not the sole reason why older male immigrants acculturate slowly—other factors that are specific to an immigrant’s country of birth (e.g., religion, cultural context) seem also to be playing a role.